Grant comes east a novel of the Civil War - Gingrich, Newt (Thomas Dunne Books/St. Martin's Press, 2004)
Grant Comes East continues the story of a Confederate victory, examining the great "what if" of American history: Could Lee have won the Battle of Gettysburg? A Confederate victory, however, would not necessarily mean that the Southern cause has gained its final triumph and a lasting peace. It is from this departure point that the story continues in Grant Comes East, as General Robert E. Lee's marches on Washington, D.C., and launches an assault against one of the largest fortifications in the world. Beyond a military victory in the field, Lee must also overcome the defiant stand of President Abraham Lincoln, who vows that regardless of the defeat at Gettysburg, his solemn pledge to preserve the Union will be honored at all cost. At the same time, Lincoln has appointed General Ulysses S. Grant as commander of all Union forces. Grant, fresh from his triumph at Vicksburg, races east, bringing with him his hardened veterans from Mississippi to confront Lee. What ensues across the next six weeks is a titanic struggle as the surviving Union forces inside the fortifications of Washington fight to hang on, while Grant prepares his counterblow. Spanning the ground from Washington to the banks of the Susquehanna, these factors will come together in a climatic, pivotal struggle.